Draft Annual Plan 1989-90 Maharashtra State - Planning Commission (Planning Commission, 1988)
The State Government took up the formulation of the Annual Plan 1989-90 in the back- Introduction, ground of the guiding principles of the 7th Five Year Plan and the guidelines issued by the Planning Commission. A draft Annual Plan of the size of Rs. 2550 crores has been prepared for submission to the planning Commission for the purposes of official level discussions in the working groups. The Planning Commission has requested the State Government to formulate the Guidelines of State’s Annual Plan 1989-90 within the broad framework of the 7th Plan.
Government of Maharashtra : Planning Department